The Effect of Corporate Governance on Tax Avoidance in Manufacturing Sector Companies on the IDX for the 2015-2019 Period - Septa Skundarian; Masyhuri Hamidi (Enrichment : Journal of Management, 2021)
Tax Avoidance is one of the tax planning strategies carried out by the company. The tax avoidance strategy is a way to reduce taxes that are legally recognized. In practice, tax avoidance is carried out based on the provisions of tax law. The purpose of this study was to determine the effect of Institutional Ownership, Independent Commissioner, Audit Committee, and Audit Quality on Tax Avoidance in the annual reports of Manufacturing Industry companies listed on the Indonesia Stock Exchange. The data used in this research is secondary data. To explain the effect of the independent variable on the dependent variable, the data obtained in this study were analyzed using panel data regression model analysis. The results of the study indicate that the independent variables jointly affect the dependent variable. However, individually, institutional ownership, independent commissioners, and audit quality have a significant positive effect on tax avoidance, while the audit committee has no significant effect on tax avoidance.